Glycosyltransferases as Markers for Early Tumorigenesis. (16th June 2015) - Andergassen, Ulrich; Liesche, Friederike; Kölbl, Alexandra C.; Ilmer, Matthias; Hutter, Stefan; Friese, Klaus; Jeschke, Udo
Abstract : Background . Glycosylation is the most frequent posttranslational modification of proteins and lipids influencing inter- and intracellular communication and cell adhesion. Altered glycosylation patterns are characteristically observed in tumour cells. Normal and altered carbohydrate chains are transferred to their acceptor structures via glycosyltransferases. Here, we present the correlation between the presence of three different glycosyltransferases and tumour characteristics. Methods . 235 breast cancer tissue samples were stained immunohistochemically for the glycosyltransferases N-acetylgalactosaminyltransferase 6 (GALNT6), β -1, 6-N-acetylglucosaminyltransferase 2 (GCNT2), and ST6 ( α -N-acetyl-neuraminyl-2, 3- β -galactosyl-1, 3)-N-acetylgalactosamine α -2, 6-sialyltransferase 1 (ST6GALNac1). Staining was evaluated by light microscopy and was correlated to different tumour characteristics by statistical analysis. Results . We found a statistically significant correlation for the presence of glycosyltransferases and tumour size and grading. Specifically smaller tumours with low grading revealed the highest incidences of glycosyltransferases. Additionally, Her4-expression but not pHer4-expression is correlated with the presence of glycosyltransferases. All other investigated parameters could not uncover any statistically significant reciprocity. Conclusion . Here we show, that glycosyltransferases can identify small tumours with well-differentiated cells; hence, glycosylation patterns could be used as a marker for early tumourigenesis. This assumption is supported by the fact that Her4 is also correlated to glycosylation, whereas the activated form of Her4 does not show such a connection with glycosylation.